Analysis of Women’s Participation in Improving Family Economy in Binjai City (Case Study of Merdeka Binjai Field Street Vendors) - Sitepu, Jessica Freety Br; Sri Herlina (Golden Ratio of Finance Management, 2026)
The purpose of this study is to determine women's participation in improving the family economy in Binjai city. The method in this study uses descriptive qualitative methods. The location of this research was carried out around the Binjai Merdeka Field. In this study, primary data will be obtained from the results of direct interviews with six street vendors around Tanah Lapang Merdeka Binjai. The data collection technique was carried out by interview. In this study, the data processing method used is qualitative data analysis. The results of the study show that the existence of women as street vendors in the fields of Binjai City plays an important role in meeting the economic needs of families, by trying to contribute significantly to the improvement of the economy and the welfare of family members. The role of female workers includes their responsibilities and obligations as housewives. Thus, in addition to carrying out formal work, they are also involved in the domestic sector, including activities such as cooking, washing clothes, washing dishes, cleaning the house, and managing the educational needs of their children. This is reflected in their consistent habits of completing household chores before leaving for work. Even though they are not able to fully meet the needs of the family, at least they can contribute to easing the burden of their husbands in earning a living. Based on the previous explanation of women's motivation to work, it can be concluded that the majority of factors that encourage their choice to work are due to financial considerations.